AB0037 Mir-155 promotes the differentiation of th17 cell by targeting ets-1 in rheumatoid arthritis. (12th June 2018) - Yin, Z.; He, W.; Chen, X.; Luo, X.; Zhang, Y.; Ye, Z.
Abstract : Background: MicroRNAs play important roles in arthritis. MiR-155 emerges as a central regulator of the immune response, but its function in autoimmune arthritis is poorly understood. Objectives: To clarify the role of miR-155 in the balance of CD4 + Th17 and Treg cell differentiations as well as how their mechanisms function in autoimmune arthritis. Methods: CD4 +T cells were in vitro isolated from DBA1 mice. The transfections of miR-155 mimics and miR-155 inhibitors in CD4 +T cells were performed for enhanced or knockdowns of miR-155 expression and RNA interference was applied to silence Ets-1 gene expression. In addition, we carried out in vivo experiments of enhanced miR-155 expression by lenti-virus mediated miR-155 (LV-miR-155) infection and silencing of miR-155 expression by lenti-virus-anti-miR-155(LV-anti-miR-155) within our well-established type II collagen (CII)-induced arthritis (CIA) mice model. The ratios of IL-17 + TH17 cells were analysed using flow cyctometry (FCM). The expressions of some key autoimmune-response of genes including RORgt, IFN-g, Ets-1, IL-17, IL-23, and Stat3 were further determined by (Taqman) Quantitative Real-time PCR and Western blotting. Initially n=6 per group if not indicated further;totally 6 groups in parallel per experiment. *p<0.05, considered as significantly;**p<0.01, considered as highly significantly. Results: For the first time we showed that miR-155 may promote Th17 cell differentiation in RA pathogenesis. Firstly, we observed that miR-155 may significantly induce the expressions of some key autoimmune-response genes including RORgt, IFN-g, IL-17, IL-23, and Stat3 but it significantly inhibited Ets-1 gene expression. 2ndly, miR-155 may in part modulates Th17 cell differentiation by targeting Ets-1 in that indeed the expression of miR-155 significantly co-related with disease index in CIA mice. Furthermore, the CIA mice with in vivo forced expression of miR-155 have significantly more Th17 cells(i.e.high ratio) and severe CIA disease index compared to their control CIA mice;strikingly, they also have a significantly higher expression of aforementioned autoimmune-response genes compared to their corresponding controls along with the response of Ets-1 exactly in a verse direction. Consistently, the CIA mice with in vivo knockdown of miR-155 expression resulted in significantly less Th17 cells and lesser severe CIA disease index compared to their control CIA mice. However, they have a significantly lower expression of above-mentioned autoimmune-response genes compared to their corresponding controls along with a response of Ets-1 in a verse direction (the data in part shown in Figure 1;sham=CIA treated with LV-nonspecific sequence). Conclusions: For the first time our data show miR-155 has a critical role in Th17 differentiation and the RA pathogenesis via targeting the Ets-1. Although it warrants further investigations, miR-155 might be a promising therapeutic target for autoimmune diseases, esp. RA. Acknowledgements: This work ws supported by National Natural Science Foundation of China #81102266. All authors listed were either involved in conception and design, or acquisition, analysis and interpretation of data, and/or writing. Each author gave their final approval of this version. Disclosure of Interest: None declared